2022
DOI: 10.1038/s41557-022-01067-z
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase formation mechanism of iodic acid as an atmospheric aerosol source

Abstract: Iodine is a reactive trace element in atmospheric chemistry that destroys ozone and nucleates particles. Iodine emissions have tripled since 1950 and are projected to keep increasing with rising O3 surface concentrations. Although iodic acid (HIO3) is widespread and forms particles more efficiently than sulfuric acid, its gas-phase formation mechanism remains unresolved. Here, in CLOUD atmospheric simulation chamber experiments that generate iodine radicals at atmospherically relevant rates, we show that iodoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 67 publications
0
47
0
Order By: Relevance
“…While the formation mechanism for HIO 3 has recently been established ( 22 ), the pathway for HIO 2 formation remains uncertain. A quantum chemical study provided a potential energy surface describing formation of HIO 2 from iodooxy hypoiodite, I 2 O 2 + H 2 O ( 30 ).…”
Section: Hio2 Accelerates Neutral Nucleationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the formation mechanism for HIO 3 has recently been established ( 22 ), the pathway for HIO 2 formation remains uncertain. A quantum chemical study provided a potential energy surface describing formation of HIO 2 from iodooxy hypoiodite, I 2 O 2 + H 2 O ( 30 ).…”
Section: Hio2 Accelerates Neutral Nucleationmentioning
confidence: 99%
“…In the marine atmosphere, iodine and sulfur precursors emitted from the ocean surface lead to the formation of both H 2 SO 4 and HIO x ( 22 ). HIO x has generally been observed at concentrations similar to or lower than H 2 SO 4 ( 6 , 18 , 21 , 23 ).…”
mentioning
confidence: 99%
“…The instrument was operational at Maïdo before, during, and after the April–June 2018 eruption of Piton de la Fournaise. 42,43 Spectra measured during the volcanic eruption were analyzed with respect to a reference spectrum measured in the absence of the volcanic plume using a DOAS spectral retrieval algorithm to retrieve SO 2 , BrO, and IO differential slant column densities (dSCDs).…”
Section: Methodsmentioning
confidence: 99%
“…In mass spectrometry laboratory studies, Martıń et al (2022) showed that new iodine containing (nano) particles and IO − 3 also form in the presence of NO − 3 and provide DH reaction data for the gas phase reactions involved. Experiments using the CERN CLOUD (Cosmics Leaving Outdoor Droplets) chamber documented the formation of HIO 3 via iodooxy hypoiodite, IOIO, as an intermediate (Finkenzeller et al, 2022) and the fast growth of HIO 3 as (nano)particles (He et al, 2021).…”
Section: Surface Seawater and Atmospheric Formation Of Io 3 - And Iod...mentioning
confidence: 99%